Microsoft IIS 6.0 : administrator's pocket consultant - Stanek, William R. (Microsoft Press, 2003)
This pocket-sized guide delivers immediate answers for the day-to-day administration of Web servers running Microsoft® IIS 6.0. Zero in on core IIS support procedures and everyday tasks using quick-reference tables, step-by-step instructions, and lists.